Guía de elaboración de Biopreparados Agroecológicos de Patagonia Norte II - Cecchini, Maria Valeria; Arancio Sidoti, Delfina; Gramaglia, Cesar Ivan; Doñate, Maria Teresa; Urraza, Maria Soledad; Gallardo, Alejandra Beatriz; Vasquez, Pablo Antonio; Guerrero, Silvana Alejandra (EEA Valle Inferior, INTA, 2024)
EEA Valle Inferior